Implemetasi Kebijakan Program bantuan Hukum Bagi Masyarakat Tidak Mampu di Pos Bantuan Hukum YLBHK-DKI Kota Tanjungpinang - Pratiwi Reka Saputri; Cica Afrita Sari; Selpi Putri Rezeki (Jurnal Indonesia Sosial Sains, 2022)
Legal assistance is needed for the people of Tanjung Pinang City because of the increasing legal problems that occur in the environment of the poor and legally blind in obtaining legal assistance by providing legal assistance for free. In an effort to realize the values of Pancasila and to realize justice for the unable to get a common position before the law, based on this, the author is interested in conducting research, namely "Implementation of the Legal Aid Program Policy for The Underprivileged Community at the Legal Aid Post of the Indonesian Justice Ambassador Legal Aid Foundation (YLBHK-DKI) Tanjungpinang City". The Research Method used by the author is empirical juridical. The data used in this study are primary data, namely observations and interviews with legal aid parties YLBHK DKI and secondary data, namely primary legal materials starting from the 1945 Constitution, Law No.16 of 2011 concerning Legal Aid, secondary legal materials in the form of journals, previous researches and relevant reference books. If referring to the implementation of the law carried out by ylbhk dki for the poor, the Legal Aid Organization or Community Assistance Institution (LBH) is the embodiment of an important principle adopted by the Criminal Procedure Code (KUHAP). The duties and responsibilities of the Legal Aid Post at YLBHK-DKI Cab KEPRI which is located in the Environment of the Tanjung Pinang State Court include providing information for every community who needs information about legal assistance and helping every community who needs legal assistance to be able to solve the legal problems they face.